Cytotoxic, antiproliferative and apoptosis-inducing activity of L-amino acid oxidase from Malaysian Calloselasma rhodostoma on human colon cancer cells - Zainal Abidin, Syafiq Asnawi; Rajadurai, Pathmanathan; Chowdhury, Md. Ezharul Hoque; Ahmad Rusmili, Muhamad Rusdi; Othman, Iekhsan; Naidu, Rakesh (Wiley-Blackwell, 2018)
The aim of this study was to investigate the cytotoxic, antiproliferative activity and the induction of apoptosis by L-amino acid oxidase isolated from Calloselasma rhodostoma crude venom (CR-LAAO) on human colon cancer cells. CR-LAAO was purified using three chromatographic steps: molecular exclusion using G-50 gel filtration resin, ion-exchange by MonoQ columnand desalted on a G25 column. The purity and identity of the isolated CR-LAAO was confirmed by SDS-PAGE and LC-MS/MS. CR-LAAO demonstrated time- and dose-dependent cytotoxic activity on SW480 (primary human colon cancer cells) andSW620 (metastatic human colon cancer cells) with an EC50 values of 6 lg/ml and 7 lg/ml at 48 hr, respectively. Quantification of apoptotic cells based on morphological features demonstrated significant increase in apoptotic cell population in both SW480 and SW620 cells which peaked at 48 hr. Significant increase in caspase-3 activity and reduction in Bcl-2 levels were demonstrated following CR-LAAO treatment. These data provide evidence on the potential anticancer activity of CR-LAAO from the venom of C. rhodostoma for therapeutic intervention of human colon cancer.